An Analysis of Usage of Different Types of Visualisation Media within a Collaborative Planning Workshop Environment. (August 2013) - Gill, Lewis; Lange, Eckart; Morgan, Ed; Romano, Daniela
Within the planning process, there is a recent trend to engage with stakeholders. Traditionally, visualisation media such as plans, sections, and physical models have been used to aid communication of planning proposals, yet technological advances now allow for virtual interactive, three-dimensional visualisations of proposals to be created. It is unclear whether these new technologies will usurp or augment the more traditional media. In an experimental setting, a set of participants in a collaborative planning workshop were introduced to a range of different visualisation media for a riverside flood-defence proposal and asked to discuss the proposal. Video recordings were made of the workshop and a questionnaire was completed by each participant. A method for capturing the time usage of each media type is presented. This shows that plans and interactive eye-level walkthroughs were the most used media types, but that user-based assessment of media might not match observed usage. These results lead to a discussion about visualisation media that should be created and further research to support the participatory planning process.